Groundwater recharge in the Bauru Aquifer System in the São Jerônimo River Basin-Triângulo Mineiro - Campos, José Claudio Viegas (2023)
The city of Gurinhatã, in the Triângulo Mineiro, located in the basin of the São Jerônimo River, a tributary of the Paranaíba River, has the Bauru Aquifer System (BAS) as the only source of water supply for the more than 5 thousand inhabitants of the urban area. Although the BAS is an important aquifer in the center-south of Brazil, few studies have been developed in its mineira portion to support its rational use. In this regard, the evaluation of groundwater recharge is fundamental for the effective management of groundwater resources. The present paper aimed to use data from the Gravity Recovery and Climate Experiment (GRACE) satellite system, to determine the mean annual BAS recharge in the São Jerônimo river basin. Concomitantly, the Water Table Fluctuation (WTF), using a piezometer from CPRM, and the hydrograph decomposition methods were applied with data from a fluviometric station. The average annual recharge for the period 2012 to 2018, obtained by the WTF method, for a specific yield (Sy) of 0.15, was 429 mm, for that of the hydrograph decomposition was 176 mm and for that of remote sensing was 408 mm. The recharge method based on GWS variable data from GRACE proved to be quite effective, having a good correspondence with the WTF method, serving as an alternative or complementary method in groundwater recharge studies.